Pengaruh Supervisi Pembelajaran dan Komitmen Kerja Terhadap Kinerja Guru di MTs Se-Kecamatan Langkaplancar Kabupaten Pangandaran Tahun 2021 - Jajang Muslim (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
Teachers must have high organizational coomitment competence. Organizational commitment shows the degree to which a teacher supports an organization and its goals in the organization. Academic supervision is serries of activities carried out by school principal to help teachers develop their ability to manage the learning process. Through this research, it is expected to obtain empirical evidence about the influence of education supervision and work commitment on teachers performance at the MTS in the all Sub-districk Langkaplancar, Pangandaran Regency. The object of research in this study is the MTS in the all Sub-districk of Langkaplancar, Pangandaran Regency because based on the observations of researchers that the phenomenon of decrease in performance achieved by teachers is influenced by education supervision and work commitment. The research method used is descriptive and verification analysis with data collection techniques using questionnaires distributed to teachers using proportionate random sampling technique. The total population is 94 people and the sample is 77 people. The result of the descriptive analysis prove that the education supervision is good, work commitment and performance of the teachers are good too. There is a positive and significant influence of education supervision and work commitment simultaneously on the performance of teachers at the MTS in the all Sub-districk Langkaplancar, Pangandaran Regency”. Thus,the quality of supervision must be improved such as icreasing class visits, clinical supervision, correctiv observations, and the suitability of learning tools with the implementation of learning. By increasing class visits, it is hoped that teacher performance will grow.